Islam dan Pembelaan Terhadap Perempuan: Studi Pemikiran Asghar Ali Engineer Teologi Pembebasan - Yola Fadila (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2023)
At the time of the Prophet we were familiar with the term "jahiliyyah", namely ignorance, there was a lot of oppression against the weak (women). Asghar Ali Engineer's liberation theology is in line with the Al-Qur'an and Hadith. Which theology of liberation does not adhere to the Status Quo (establishment) system, because Islam is a force for liberation against exploitation, oppression and tyranny. Liberation Theology first appeared in Europe in the twentieth century, intended to see the role of religion in liberating humans. Second, the implementation of Asghar Ali Engineer's liberation theology concept, there are three concepts such as Jihad, Tawhid, and Faith. Humans are free creatures that are free to determine their own destiny. Without these three things it will not be realized to defend the Mustad'afin and women, the three concepts have one goal and path, namely to lead to the way of Allah SWT and free everything from oppression. This research uses the library research study method and a qualitative approach. Through liberation theology, we can know that liberation theology is in line with the Al-Qur'an and Hadith.